Antibacterial Evaluation and Phytochemical Screening of Datura metel Leaf Extracts against Bacterial Pathogens - Saranraj, P (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTInfectious disease can become a threat to public health in this world. The use of medicinal plants for the treatment of various diseases is an old practice in most countries and it still offers a enormous potential source of new anti-infective agents. The present study was conducted to evaluate the antibacterial potentiality of ethanol and ethyl acetate solvent extracts of mature leaves of Datura metel against nine pathogenic bacterial isolates viz., Staphylococcus aureus, Bacillus subtilis, Bacillus cereus, Escherichia coli, Salmonella typhi, Shigella flexneri, Klebsiella pneumoniae, Vibrio cholerae and Pseudomonas aeruginosa. The turbidity of the bacterial inoculums was compared with 0.5 Mc Farland standards and the antibacterial potential of Datura metel ethanol extract was tested by using Agar well diffusion method. The ethanol extract of Datura metel (100 mg/ml) showed maximum zone of inhibition (26 mm) against Pseudomonas aeruginosa, Escherichia coli and Bacillus subtilis. Staphylococcus aureus showed less zone of inhibition (8 mm). The ethyl acetate extract of Datura metel (100 mg/ml) showed maximum zone of inhibition (19 mm) against Escherichia coli. There was no zone of inhibition against Pseudomonas aeruginosa. Phytochemical tests were performed and showed that the antibacterial activity of Datura metel plant leaves was due to the presence of phytochemical compounds like alkaloids, tripenoid, steroids, flavonoid, triterpenes, phenolic compounds and tannins.